Trends in Varietal Diversity of Main Staple Crops in Asia and Africa and Implications for Sustainable Food Systems - Gatto, Marcel; de Haan, Stef; Laborte, Alice; Bonierbale, Merideth; Labarta, Ricardo; Hareau, Guy (Frontiers in Sustainable Food Systems, 2021)
Crop species and varietal diversity on farm have the potential to trigger multiple regulating and provisioning ecosystem services. The latter is commonly assessed through targeted studies covering a select number of geographies and crop species, precluding comparisons across crops and at scale. This study draws on a large dataset on the varietal release dynamics for 11 major food crops in 44 countries of Asia and Africa to assess trends in diversity across crops and regions with a 50-year perspective. Our results show an increasing reduction of crop varietal diversity linked to the spatial displacement of traditional landraces. This trend occurs at a faster rate in Asia than in Africa. So-called mega varieties tend to increasingly dominate agricultural landscapes, adding to spatial homogeneity. We further found a negative association between varietal richness and its relative abundance, challenging the relationship between crop improvement and varietal diversity. Our results show that among cereal, pulse, and root and tuber crops, varietal diversity is lowest for cereals in Asia and highest for root and tubers in Africa. The analysis contributes new information useful to prioritize crops for which increasing varietal diversity may lead to more sustainable food systems.